Model Range of Unified Power Drives for Commercial Electric Transport - Sergey N. Poddubko; Alexander V. Belevich; Mikhail V. Kalinin; Pavel E. Shabanau (Механика машин, механизмов и материалов)
The article considers the creation of a model range of unified electric power drives for commercial electric vehicles. The peculiarity of the work is the realization of the concept of reducing the cost of production of electromechanical power units (EMPU) of electric vehicles by unification of units and components included in its composition. When forming a number of unified electric power drives, the components were subjected to a set of design, layout, technological and economic requirements ensuring the production on their basis of cargo or passenger electric vehicles with gross weight from 3.5 to 12 t, which corresponds to vehicle categories N1, N2, M2, M3. The developed main components of the unified EMPU include: asynchronous three-phase traction electric motors with power range from 80 to 300 kW, torque range from 250 to 1,000 N·m respectively, output shaft rotation frequency of 9,000 rpm and liquid cooling of stator and rotor; inverters designed to control traction motors with input voltage range from 300 to 900 V, output phase current range from 200 to 600 A and liquid-cooled power keys; reduction gearboxes with gear ratio from 3 to 4.5 and step gearboxes with the number of gears from 2 to 4. The result of works on unification of electric power drives for commercial transport also is a number of standard designs of parts and units and assembly units; normative and technical support of control (tests, analysis, measurements) of certification and quality assessment of products; establishment of requirements for technological processes, including for reduction of material, energy and labor intensity to ensure the use of low-waste technologies. When creating the electric truck MAZ-4381EE, corresponding to the vehicle category N2, the EMPU was used as a part of electric motor TAEM 130 with capacity of 130 kW and two-stage shaft gearbox. The created prototype of electric truck is characterized by almost complete localization, providing import independence of most components and intellectual component of the car.